Report of the Committee on Streamlining the Requirement of Inspection of Industrial Units Under Different Acts - Planning Commission (Planning Commission Government of India, 2005)
The Report of the Committee on Streamlining the Requirement of Inspection of Industrial Units, commissioned by the Planning Commission in December 2005, addresses the challenges posed by multiple inspections under various regulatory frameworks. The study highlights the excessive burden on industrial units, with factories undergoing an average of 37 inspections annually, sometimes up to 67, leading to operational inefficiencies and bureaucratic delays. Key findings point to overlapping inspections, extensive record-keeping requirements, and India’s relatively low international ranking in regulatory efficiency. Recommendations include unified inspections, self-certification programs for compliant industries, simplified record-keeping, third-party inspections, and enhanced training for inspectors. The report emphasizes that implementing these reforms would reduce administrative burdens, improve compliance, foster industrial competitiveness, and align India with global best practices, thereby supporting sustainable economic growth.
Planning Commission Government of India December, 2005
Keywords: Industrial Inspections; Streamlining Compliance; Regulatory Reform; Inspector Raj; Self-Certification; Unified Inspections; Record-Keeping Simplification; Third-Party Inspections; Industrial Units; Compliance Burden; Regulatory Efficiency; Industrial Competitiveness